MODERN METHODOLOGY FOR DEVELOPING FUNCTIONAL FOOD TECHNOLOGY - Stetsenko, Nataliia; Goyko, Iryna; Bashta, Alla (SWorld-Ger Conference proceedings, 2024)
The paper considers a comprehensive methodological approach to the creation of functional food products, which allows for a reasoned and well-founded choice of the main object, as well as functional ingredients or natural types of raw materials containing